Problematika Perbedaan Nilai Kriteria Ketuntasan Minimal (KKM) Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti Pada Kurikulum 2013 (Studi kasus di SMK Muhammadiyah 1 Ciputat Tangerang Selatan) - Wiguna Yuniarsih; Fajar Syarif; Fahruroji Fahruroji (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2022)
The purpose of this study was to describe the difference in KKM scores between majors/skills programs, as well as the inhibiting and supporting factors in Islamic religious education subjects at SMK Muhammadiyah 1 Ciputat, South Tangerang. This study used qualitative research methods. Data collection techniques through observation, interviews, and documentation. While the data analysis technique used descriptive analysis. The results of this study indicate that; 1) The difference in the KKM value of each department with the smallest KKM value of each marketing department is the KKM value for class X 77.67, XI 70.33 and XII 70.33. While the highest KKM value is in the accounting department with a KKM value of class X 80.67, XI 75.67 and XII 76.67. 2) Supporting factors include facilities and infrastructure as well as teachers who master the learning material. While the inhibiting factor is the level of intelligence of students who are different so that the assessment of PAI and BP subjects does not reach the KKM.